Evaporation Kinetics of Polyol Droplets: Determination of Evaporation Coefficients and Diffusion Constants. Issue 22 (22nd November 2017) - Su, Yong‐Yang; Marsh, Aleksandra; Haddrell, Allen E.; Li, Zhi‐Ming; Reid, Jonathan P.
Abstract: In order to quantify the kinetics of mass transfer between the gas and condensed phases in aerosol, physicochemical properties of the gas and condensed phases and kinetic parameters (mass/thermal accommodation coefficients) are crucial for estimating mass fluxes over a wide size range from the free molecule to continuum regimes. In this study, we report measurements of the evaporation kinetics of droplets of 1‐butanol, ethylene glycol (EG), diethylene glycol (DEG), and glycerol under well‐controlled conditions (gas flow rates and temperature) using the previously developed cylindrical electrode electrodynamic balance technique. Measurements are compared with a model that captures the heat and mass transfer occurring at the evaporating droplet surface. The aim of these measurements is to clarify the discrepancy in the reported values of mass accommodation coefficient ( α M, equals to evaporation coefficient based on microscopic reversibility) for 1‐butanol, EG, and DEG and improve the accuracy of the value of the diffusion coefficient for glycerol in gaseous nitrogen. The uncertainties in the thermophysical and experimental parameters are carefully assessed, the literature values of the vapor pressures of these components are evaluated, and the plausible ranges of the evaporation coefficients for 1‐butanol, EG, and DEG as well as uncertainty in diffusion coefficient for glycerol are reported. Results show that α M should be greater than 0.4, 0.2, and 0.4 for EG, DEG, and 1‐butanol, respectively. The refined values are helpful for accurate prediction of the evaporation/condensation rates. Key Points: The mass accommodation coefficients should be greater than 0.4, 0.2, and 0.4 for EG, DEG, and 1‐butanol, respectively The relative standard deviation of the calculated diffusion constant for glycerol is improved from ±8% to between −3% and 1%